Intertidal chitons (Mollusca: Polyplacophora) from the rocky coastline of Guerrero, México, with the description of a new species - Reyes-Gómez, Adriana; Flores-Garza, Rafael; Galeana-Rebolledo, Lizeth; Hernández-Vera, Gerardo; Galván-Villa, Cristian M.; Torreblanca-Ramírez, Carmina; Flores-Rodríguez, Pedro; García-Ibañez, Sergio; Ríos-Jara, Eduardo (Zootaxa, 2022)
Chitons from southern México have been poorly documented hitherto and little is known about the species present in this region. Here we report 12 intertidal to shallow subtidal species in six families and nine genera. Chiton articulatus, Chiton albolineatus, and Ischnochiton muscarius were numerically the most common species, accounting for 29%, 27%, and 26% of individuals found, followed by Chaetopleura lurida (7%) and Stenoplax limaciformis (3%). The remainder of the species obtained were present with between 0.5 and 2% of the total sample. Eight species are distributed along the Tropical Eastern Pacific, and four species (I. muscarius, C. albolineatus, C. articulatus, and Lepidochitona acapulcoensis sp. nov.) are endemic to the Mexican subprovince, distributed from Mazatlán to Oaxaca. A morphological comparison of Guerrero chitons with those from several points along the Mexican Tropical Pacific and La Paz Baja California Sur, revealed important variations. Specimens of Chaetopleura lurida from Guerrero contrasts in the valve sculpturing density and arrangement when compared to those from Mazatlán and Oaxaca. Callistochiton elenensis from Guerrero exhibits fewer ribs on the head valve and postmucronal area of the tail valve than specimens from La Paz, Baja California Sur. Color pattern differences were identified for Mazatlán and Oaxaca specimens of I. muscarius, C. articulatus, and C. albolineatus. Details are presented for the valve tegmentum, girdle elements, and radula for each species. In addition, we herein describe Lepidochitona acapulcoensis sp. nov. as a new species using barcode (cox1) and morphological data.